Associations between alcohol use and HIV care cascade outcomes among adults undergoing population-based HIV testing in East Africa. (1st March 2020) - Puryear, Sarah B.; Balzer, Laura B.; Ayieko, James; Kwarisiima, Dalsone; Hahn, Judith A.; Charlebois, Edwin D.; Clark, Tamara D.; Cohen, Craig R.; Bukusi, Elizabeth A.; Kamya, Moses R.; Petersen, Maya L.; Havlir, Diane V.; et al.
Abstract : Objective: To assess the impact of alcohol use on HIV care cascade outcomes. Design: Cross-sectional analyses. Methods: We evaluated HIV care cascade outcomes and alcohol use in adults (≥15 years) during baseline (2013--2014) population-based HIV testing in 28 Kenyan and Ugandan communities. 'Alcohol use' included any current use and was stratified by Alcohol Use Disorders Identification Test-Concise (AUDIT-C) scores: nonhazardous/low (1--3 men/1--2 women), hazardous/medium (4--5 men/3--5 women), hazardous/high (6--7), hazardous/very-high (8--12). We estimated cascade outcomes and relative risks associated with each drinking level using targeted maximum likelihood estimation, adjusting for confounding and missing measures. Results: Among 118 923 adults, 10 268 (9%) tested HIV-positive. Of those, 10 067 (98%) completed alcohol screening: 1626 (16%) reported drinking, representing 7% of women (467/6499) and 33% of men (1 159/3568). Drinking levels were: low (48%), medium (34%), high (11%), very high (7%). Drinkers were less likely to be previously HIV diagnosed (58% [95% CI: 55--61%]) than nondrinkers [66% (95% CI: 65–67%); RR: 0.87 (95% CI: 0.83–0.92)]. If previously diagnosed, drinkers were less likely to be on ART [77% (95% CI: 73–80%)] than nondrinkers [83% (95% CI 82–84%); RR: 0.93 (95% CI: 0.89–0.97)]. If on ART, there was no association between alcohol use and viral suppression; however, very-high-level users were less likely to be suppressed [RR: 0.80 (95% CI: 0.68–0.94)] versus nondrinkers. On a population level, viral suppression was 38% (95% CI: 36–41%) among drinkers and 44% (95% CI: 43–45%) among nondrinkers [RR: 0.87 (95% CI 0.82–0.94)], an association seen at all drinking levels. Conclusion: Alcohol use was associated with lower viral suppression; this may be because of decreased HIV diagnosis and ART use.